Rustlers' rhapsody [videorecording (Blu-Ray)] - Berenger, Tom, 1949-; Bailey, G. W., 1945-; Griffith, Andy, 1926-2012; Henner, Marilu (KL studio classics., 2025)
The Wild West goes wacko when the Greatest Fast-Drawin', Fancy-Dressin', Silver-Spurred, Geetar Playin', Singing Cowboy movie matinee idol Rex O'Herlihan hits the saddle in this cockeyed, affectionate send-up of the '40s B-movie Western.